Can We Develop a Professional Ethic of Service in Education? - Todd, Reese H. (International Journal of Research on Service-Learning in Teacher Education, 2010)
The study describes the use of service-learning pedagogy to develop an ethic of service in a teacher preparation program and to enhance mutually beneficial community partnerships. A group of instructors modified assignments for the field-based course, using an action research plan that emphasized the role of community engagement among professional educators. Students gained knowledge and skills in observing and identifying needs within the school, developing plans to meet needs, providing service with school partners, and reflecting on the experiences. School partners gained active citizens adding recognizable value to the mission of the school community. As a result of the service-learning projects, administrators and teachers welcomed more preservice teachers from the university into their schools. The community engagement emphasis benefitted school partners while students acquired valuable practical knowledge as future teachers.